Numerical and experimental comparison between two different blade configurations of a wind generator. (February 2016) - Alaimo, Andrea; Lo Iacono, Francesco; Navarra, Giacomo; Pipitone, Giovanni
Abstract: This paper presents a comparison between the structural behaviour of a wind generator with straight blades and a composite prototype of a wind generator with helical blades. Numerical structural analyses are performed by means of FEM models by using ANSYS® Mechanical™ software package. Furthermore, laboratory dynamic experimental tests are carried out on real scale specimens of the two wind generator configurations in order to find their modal properties in terms of natural frequencies and modal shapes. The results of the experimental campaign are then used to update the numerical models by minimizing an objective function. Total stresses and deformations of the two wind generator configurations, coming from the updated numerical models, are evaluated and compared to quantitatively point out the improvement of the structural behaviour obtained by the use of composite materials.